A novel development of green ultra-high performance concrete (UHPC) based on appropriate application of recycled cementitious material. (10th July 2020) - Qian, Diao; Yu, Rui; Shui, Zhonghe; Sun, Yu; Jiang, Chunyuan; Zhou, Fengjiao; Ding, Mengxi; Tong, Xuansheng; He, Yongjia
Abstract: Recycled construction waste cementitious material (RCWCM) can be considered as a kind of waste solid with potential cementitious characteristics. In the past, landfill and stacking methods were generally used for treating this type of wastes, which is harmful for the sustainable development of construction industry. Hence, based on this premise, an effective method for developing a green Ultra-High Performance Concrete (UHPC) by incorporating RCWCM is addressed in this study. Specifically, dehydrated cementitious powder (DCP) is obtained from heating treatment of RCWCM. Then, the DCP is used to gradually replace the cement and included in the design of UHPC based on Modified Andreasen & Andersen (MAA) particle packing model. Afterwards, the physical and chemical characteristics of the newly produced UHPC are evaluated. The results show that when DCP is used to replace up to 25% cement, the variation of UHPC compressive strength is difficult to be noticed. Corresponding to that, the microstructure and durability of the developed green UHPC are also advanced when the added DCP content is less than 25%. Additionally, the ecological assessment shows that the UHPC incorporating DCP has a relatively small impact on the environment, which provides a broad prospect for the future sustainable development of UHPC. Graphical abstract: Image 1 Highlights: The RCWCM is incorporated in the production of UHPC. The adding of DCP can significantly affect the flowability of UHPC. Optimal amount of DCP is beneficial for the strength of UHPC. Optimal amount of DCP is beneficial for the microstructure of UHPC. Utilization of DCP is beneficial for the sustainable development of UHPC.